1999
DOI: 10.1111/j.1365-2621.1999.tb15933.x
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing Oil Uptake of Doughnuts During Deep‐fat Frying Using Curdlan

Abstract: The ability of the dry ingredient curdlan (0% to 1% w/w) to lower oil uptake and moisture loss in doughnuts during deep-fat frying was compared with that of cellulose derivatives. An index expressing the ratio between oil uptake and moisture loss was developed. The addition of curdlan showed a linear effect on reducing each parameter (p < 0.001) within a range of 0% to 0.5%. This effect of curdlan probably is attributed to its thermal gelling property, and the heat-induced gel during frying probably functioned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
4

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 13 publications
0
32
0
4
Order By: Relevance
“…Lowering expansion was followed by decrease in specific surface area and amount of pores in the fried crackers, which does not allow enough room for oil uptake; this is supported by the results of the texture analysis (Maneerote et al, 2009;Nurul et al, 2009). Additionally, hydrocolloids, which facilitate the natural barrier properties of starch or protein, reduce oil absorption through film formation at temperatures above their incipient gelation temperature during deep-fat frying (Funami, Funami, Tawada, & Nakao, 1999;Singthong & Thongkaew, 2009). It has been reported that GBF contains 12 g/100 g non-starch polysaccharides (dry basis) (Suntharalingam & Ravindran, 1993), which may help in reducing oil uptake.…”
Section: Resultsmentioning
confidence: 98%
“…Lowering expansion was followed by decrease in specific surface area and amount of pores in the fried crackers, which does not allow enough room for oil uptake; this is supported by the results of the texture analysis (Maneerote et al, 2009;Nurul et al, 2009). Additionally, hydrocolloids, which facilitate the natural barrier properties of starch or protein, reduce oil absorption through film formation at temperatures above their incipient gelation temperature during deep-fat frying (Funami, Funami, Tawada, & Nakao, 1999;Singthong & Thongkaew, 2009). It has been reported that GBF contains 12 g/100 g non-starch polysaccharides (dry basis) (Suntharalingam & Ravindran, 1993), which may help in reducing oil uptake.…”
Section: Resultsmentioning
confidence: 98%
“…Barley is high in b-glucan (Temelli, 1997) and low uptake of oil could be due to its thermal gelling property. Heat induced gel during frying probably functioned as an oil and moisture barrier (Funami, Funami, Tawada, & Nakao, 1999).…”
Section: Proximate Compositionmentioning
confidence: 99%
“…However, these products contain a substantial amount of fat, some as much as 45% (Funami & Funami, 1999;Saguy & Pinthus, 1995), because food, especially those that are naturally low in fat, absorb large amounts of fat during deep fat frying. The degree of oil absorption is significantly affected by various factors such as process conditions (temperature, time), pretreatment of food, physico-chemical characteristics of food, oil origin, chemical composition of oil and others.…”
Section: Introductionmentioning
confidence: 98%